Can the angle between optic nerves indicate whether optic chiasm is prefixed, normofixed or postfixed? An anatomical study with radiologic and neurosurgical implications. - Yohannan, Doris; Krishnapillai, Renuka; Suresh, Romi; Ramnarayan, Shobha; Peethambaran, Anil; John, Neelankavil (Surgical & Radiologic Anatomy, 2016)
Purpose: The objective of this study was to measure the angle ( Interneural angle, INA) between intracranial segments of optic nerves (ISON), and to look for any relation between it and the relative anteroposterior location (RAPL) of the optic chiasm (OC)-viz. prefixed, normofixed and postfixed. Methods: The sample comprised of 100 autopsy specimens from South Indian population. INA was measured using software-aided processing of digital photographs. Length of the ISON was measured on each side using Vernier calipers. RAPL of the OC was noted during dissection. These were analysed with statistical methods. Results: RAPL of OC was found to be prefixed in 24 %, normofixed in 65 % and postfixed in 11 %. The INA had an overall mean of 69.9° (SD 9.29°). ANOVA confirmed statistically significant difference in INA among different groups; the corresponding mean value for the group was as follows: 79.61° (prefixed), 68.10° (normofixed) and 59.48° (postfixed). ROC curve was plotted for the use of various 'cut off' values of INA to 'diagnose' prefixed OC; an INA ≥71.4° was seen to diagnostically correlate with prefixed OC with 83.3 % sensitivity and 75 % specificity. Conclusions: The INA is wider when OC is prefixed, intermediate when normofixed and narrowed when postfixed. This observation throws light on the possibility of using INA as a marker of RAPL of OC. As INA can be measured in axial MRI sections, it can be used in differentiation of the cases with prefixed OC from others during pre-operative work up for pituitary surgeries and to identify individuals 'at risk' during subfrontal approach for pituitary lesions.